Optimized monoclonal antibody treatment against ELTD1 for GBM in a G55 xenograft mouse model. Issue 2 (21st December 2019) - Zalles, Michelle; Smith, Nataliya; Ziegler, Jadith; Saunders, Debra; Remerowski, Shannon; Thomas, Lincy; Gulej, Rafal; Mamedova, Nadya; Lerner, Megan; Fung, Kar‐Ming; Chung, Junho; Hwang, Kyusang; et al.
Abstract: Glioblastoma is an aggressive brain tumour found in adults, and the therapeutic approaches available have not significantly increased patient survival. Recently, we discovered that ELTD1, an angiogenic biomarker, is highly expressed in human gliomas. Polyclonal anti‐ELTD1 treatments were effective in glioma pre‐clinical models, however, pAb binding is potentially promiscuous. Therefore, the aim of this study was to determine the effects of an optimized monoclonal anti‐ELTD1 treatment in G55 xenograft glioma models. MRI was used to assess the effects of the treatments on animal survival, tumour volumes, perfusion rates and binding specificity. Immunohistochemistry and histology were conducted to confirm and characterize microvessel density and Notch1 levels, and to locate the molecular probes. RNA‐sequencing was used to analyse the effects of the mAb treatment. Our monoclonal anti‐ELTD1 treatment significantly increased animal survival, reduced tumour volumes, normalized the vasculature and showed higher binding specificity within the tumour compared with both control‐ and polyclonal‐treated mice. Notch1 positivity staining and RNA‐seq results suggested that ELTD1 has the ability to interact with and interrupt Notch1 signalling. Although little is known about ELTD1, particularly about its ligand and pathways, our data suggest that our monoclonal anti‐ELTD1 antibody is a promising anti‐angiogenic therapeutic in glioblastomas.